2019
DOI: 10.1101/746776
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In vitrohepatitis C virus infection and hepatic choline metabolism

Abstract: Choline is an essential nutrient required for normal neuronal and muscular development, as well as homeostatic regulation of hepatic metabolism. In the liver, choline is incorporated into the main eukaryotic phospholipid, phosphatidylcholine (PC) and can enter one carbon metabolism via mitochondrial oxidation. Hepatitis C virus (HCV) is a hepatotropic positive-strand RNA virus that similar to other positive-strand RNA viruses can impact phospholipid metabolism. In the current study we sought to interrogate the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…HCV requires host factors to complete its life cycle, and virus-host factor interaction and host responses to the virus have an impact on host genes and consequently cause HCV-associated liver diseases. Gene expression changes caused by HCV have been widely reported using microarray ( Blackham et al, 2010 ; Liu et al, 2010 ; Woodhouse et al, 2010 ) and disrupted pathways, including lipid metabolism ( Blackham et al, 2010 ; Woodhouse et al, 2010 ), oxidative stress ( Liu et al, 2010 ), and choline metabolism ( Gobeil Odai et al, 2020 ) have been observed. These findings provide partial understanding of the viral pathogenesis, such as steatosis.…”
Section: Introductionmentioning
confidence: 99%
“…HCV requires host factors to complete its life cycle, and virus-host factor interaction and host responses to the virus have an impact on host genes and consequently cause HCV-associated liver diseases. Gene expression changes caused by HCV have been widely reported using microarray ( Blackham et al, 2010 ; Liu et al, 2010 ; Woodhouse et al, 2010 ) and disrupted pathways, including lipid metabolism ( Blackham et al, 2010 ; Woodhouse et al, 2010 ), oxidative stress ( Liu et al, 2010 ), and choline metabolism ( Gobeil Odai et al, 2020 ) have been observed. These findings provide partial understanding of the viral pathogenesis, such as steatosis.…”
Section: Introductionmentioning
confidence: 99%